Principles of Qur’an-Based Children’s Education for Single Moms (Thematic Analysis of Maryam’s Story in the Qur’an) - Hafif Mukhozin; M. Aufa; Thoriq Mumtaz (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Single moms face the dual challenge of raising children while managing other responsibilities, necessitating an approach rooted in moral and spiritual values. This study aims to explore Qur’an-based principles of child education for single moms through a thematic analysis of Maryam’s story. The research focuses on the moral, spiritual, and educational values embedded in the story and their implementation in raising children amidst these dual challenges. The study employs a library research method with a thematic exegesis (tafsir maudhu’i) approach, using primary data from Qur’anic verses related to Maryam’s story and secondary data from exegesis texts, academic literature, and scholarly articles. The findings reveal that Maryam’s story teaches the significance of steadfast faith, moral exemplarity, and a balance between effort and reliance on God in child-rearing. These values inspire single moms to nurture children with resilience and faith while maintaining family harmony. The study underscores the relevance of Qur’anic principles in modern contexts, particularly in addressing social and economic challenges. It is expected to serve as a practical guide for single moms and a reference for academics and Islamic educational institutions in developing educational models based on Qur’anic values.